Search for WZ resonances in the fully leptonic channel using pp collisions at s√ = 8 TeV with the ATLAS detector - Onofre, A. (2014)
A search for resonant WZ production in the ℓνℓ′ℓ′ℓνℓ′ℓ′ (ℓ,ℓ′=e,μℓ,ℓ′=e,μ) decay channel using 20.3 fb−1 of View the MathML sources=8 TeVpp collision data collected by the ATLAS experiment at LHC is presented. No significant deviation from the Standard Model prediction is observed and upper limits on the production cross sections of WZ resonances from an extended gauge model W′W′ and from a simplified model of heavy vector triplets are derived. A corresponding observed (expected) lower mass limit of 1.52 (1.49) TeV is derived for the W′W′ at the 95% confidence level.